Tradução e ceticismo. - Helena Franco Martins (Cadernos de Tradução, 2005)
This paper discusses the limits between translation and manipulation, in the context of the broader debate on the role of skepticism within contemporary perspectives on language and meaning. It shows how the spread of anti-imanentist views may invite skepticism, exploring on the other hand the possibility of an anti-imanentist response to the skeptic, mainly based on S. Cavell’s Wittgensteinian reflections on this issue. The impact of skeptical doubt on the field of translation is analyzed in the light of the previous discussion, and the case is made for not taking skepticism towards the distinction between translating and manipulating as a necessary result of renouncing the belief in imanent and transcendental meaning. Keywords: translation, manipulation, anti-imanentism, skepticism.